Perencanaan Rotasi Bekisting dengan Building Information Modelling (BIM) (Studi Kasus Gedung Kuliah A Fakultas Kedokteran Universitas Lampung) - Putra Sianipar, Michael Yuda Cen; Bayzoni, Bayzoni; Siregar, Amril Ma'ruf; Husni, Hasti Riakara (Universitas Lampung, 2023)
This research plans the volume and rotation of formwork. Formwork modelling in the LectureBuilding A project of Faculty of Medicine, University of Lampung used the concept of BuildingInformation Modeling (BIM). This research aims to model formwork for plate, column and shearwall works and determine the rotation method used in the Lecture Building A project of Faculty ofMedicine, University of Lampung by applying the concept of Building Information Modeling(BIM). The results showed that the formwork volume in Revit was smaller than the BoQ volume inthe project. Expressed the difference in column volume results by 285.03 m2 (36.31%), platevolume of 205.13 m2 (30.63%), and shear wall volume of 26.138 m2 (13.4%). And in theformwork output of the beam structure with the sampling method of the deck floor +25 beam typeB2 (400x250), the total volume result is 33.2639 m2 (4.38%). And then results of the rotationanalysis total volume of formwork required in the shear wall structure amounted to 67,554 m2(40.01 %), 213.39 m2 (42.67 %) of columns, and 195.37 m2 (42.06 %) of plates.Keywords: Formwork, Building Information Modelling (BIM), Volume